The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1364/josaa.24.000597
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor waveguides and effective retinal image quality

Abstract: Individual photoreceptor waveguiding suggests that the entire retina can be considered as a composite fiber-optic element relating a retinal image to a corresponding waveguided image. In such a scheme, a visual sensation is produced only when the latter interacts with the pigments of the outer photoreceptor segments. Here the possible consequences of photoreceptor waveguiding on vision are studied with important implications for the pupil-apodization method commonly used to incorporate directional effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
2
43
0
1
Order By: Relevance
“…An initial light distribution entering the cell was taken as a diffraction pattern from the eye's pupil, which is broadened by corneal aberrations, to create an average Gaussian distribution of B40 mm width 24,25 . Next, the field was propagated down the medium, plane by plane, where every step was of 0.13 mm length.…”
Section: Resultsmentioning
confidence: 99%
“…An initial light distribution entering the cell was taken as a diffraction pattern from the eye's pupil, which is broadened by corneal aberrations, to create an average Gaussian distribution of B40 mm width 24,25 . Next, the field was propagated down the medium, plane by plane, where every step was of 0.13 mm length.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the investigation of differences in cone reflectance between pathological and healthy retinas is still limited to a few isolated studies [20,21]. In addition, studies have demonstrated that cones in the central retina may vary their sensitivity or pointing direction in order to compensate for the eye's internal aberrations [22] or deterioration in the nearby cone's functionality [23] and that cones in the peripheral retina may vary their pointing direction depending on the position of the center of the illumination pupil [24]. The use of AO Optical Coherence Tomography (OCT) has also provided information on the dependence of the reflectance on depth in the inner cone interfaces, leading for the first time to a 3D characterisation of the cone reflectance [14].…”
Section: Introductionmentioning
confidence: 99%
“…This may be at odds with the current understanding that light is focused at the inner segment entrance for best vision. The optical properties of the inner segment in itself, however, and possible cellular focusing effects [47] may support the image guidance [48] and light concentration towards the outer segment. This volumetric optimization of light overlap with the available pigments suggests that in dim light the best focus is possibly shifted forward towards the first layers of the outer segments by approximate −0.1 diopters.…”
Section: Discussionmentioning
confidence: 98%